2005
DOI: 10.1038/nn1620
|View full text |Cite
|
Sign up to set email alerts
|

Competing waves of oligodendrocytes in the forebrain and postnatal elimination of an embryonic lineage

Abstract: The developmental origin of oligodendrocyte progenitors (OLPs) in the forebrain has been controversial. We now show, by Cre-lox fate mapping in transgenic mice, that the first OLPs originate in the medial ganglionic eminence (MGE) and anterior entopeduncular area (AEP) in the ventral forebrain. From there, they populate the entire embryonic telencephalon including the cerebral cortex before being joined by a second wave of OLPs from the lateral and/or caudal ganglionic eminences (LGE and CGE). Finally, a third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

61
1,330
8
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,030 publications
(1,411 citation statements)
references
References 50 publications
61
1,330
8
12
Order By: Relevance
“…The small proportion of Olig2+/PSA-NCAM+ cells probably represents neuronal progenitors, although it is possible that a subpopulation of oligodendrocyte progenitors during very early stages of development expresses PSA-NCAM. This would be consistent with recent reports describing various oligodendrocyte progenitors subpopulations in rodents (Spassky et al, 2000;Kessaris et al, 2006, Parras et al, 2007, and possibly in humans, as we discussed previously (Jakovcevski and Zecevic, 2005b). The fact that at midgestation glia cell populations in the human brain do not express PSA-NCAM, as has been shown in rodents, might be due to either inter-species differences or difference in studied stages of development.…”
Section: Discussionsupporting
confidence: 92%
“…The small proportion of Olig2+/PSA-NCAM+ cells probably represents neuronal progenitors, although it is possible that a subpopulation of oligodendrocyte progenitors during very early stages of development expresses PSA-NCAM. This would be consistent with recent reports describing various oligodendrocyte progenitors subpopulations in rodents (Spassky et al, 2000;Kessaris et al, 2006, Parras et al, 2007, and possibly in humans, as we discussed previously (Jakovcevski and Zecevic, 2005b). The fact that at midgestation glia cell populations in the human brain do not express PSA-NCAM, as has been shown in rodents, might be due to either inter-species differences or difference in studied stages of development.…”
Section: Discussionsupporting
confidence: 92%
“…35 As the expression of p57Kip2 was found to be high in the ventral telencephalon (Figure 2a), it is tempting to speculate whether a potential role for p57Kip2 could be to repress neuronal differentiation to secure proper oligodendrocyte proliferation, specification, and/or differentiation. An expression-level-dependent role for p57Kip2 in Notch-regulated oligodendrocyte specification in the ventral spinal cord has been suggested from elegant experiments in zebrafish, 34 and it was recently shown that proper levels of p57Kip2 is critical for correct proliferation as well as differentiation of primary oligodendrocyte progenitor cells as well as Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cortico-cerebral histogenesis is an extremely complex process, characterized by a well-defined spatial [1][2][3][4][5], temporal [6], and histogenetic plan [7]. Precursors giving rise to mature cell types include neural stem cells (NSCs), able to self-renew indefinitely and to generate all the mature cell types; and NSC-derived, lineage-restricted progenitors, characterized by more limited self-renewal potentials and more restricted histogenetic potencies.…”
Section: Introductionmentioning
confidence: 99%